MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA MENGGUNKAN MEDIA WORD WALL KELAS II SD NEGERI 067240 MEDAN TEMBUNG - Florida Yani Simanullang; Sri Wahyuni; Rahmat Hasibuan (STKIP Subang, 2024)
This research is an action regarding the use of word wall media to improve Indonesian language learning outcomes on my family tree material for class II students at SDN 067240 Medan Tembung for the 2024/2025 academic year. This research is classroom action research. Data collection was obtained using test methods, observation guides and field notes. Analysis of test results shows that students experienced consistent increases in learning outcomes in both cycles when compared with learning outcomes during the preliminary study. Success criteria were also achieved in the implementation of actions in both cycles. Supporting data through observation also shows that the use of word wall media can increase student activity in learning as indicated by obtaining high activity scores. The use of word wall media in Indonesian language learning has been proven to be able to increase learning outcomes and student activity. The learning outcomes in the pre-cycle were 20%, increasing in cycle I to 60% and increasing again in cycle II to 87% in Indonesian language learning.